STUDY OF MAJJADHATU IN MADHUMEHA WITH SPECIAL REFERENCE TO DIABETIC NEUROPATHY (International Journal of Ayurveda and Pharma Research, 2019)
Prameha is described as the one of the disease in Mahagada by different Acharyas. Majja Dhatudushti is one of the factor in Prameha (in Pramehadushyas Majjadhatu is included). However the term ‘Majja’ has become synonymous with nervous system, which is encased within bone like bone marrow. The Majja Dhatu is associated with entire nervous system. The nervous system and the bone marrow are treated as homologous structures in Ayurveda. According to Ayurveda, ultimately all Prameha are finally complicated into Madhumeha which can say diabetes mellitus. Diabetic mellitus can be called an epidemic of the 21st century, as The World Health Organization estimates. As estimated, about 60 to 70% of people with diabetes have some form of neuropathy, but not all with neuropathy have symptoms. There are different types of diabetic neuropathies like peripheral, autonomic, focal, etc, among these peripheral neuropathy is most common seen in the diabetics. In this study 50 diabetic patients were selected. Assessment of Majja Dhatu Dushti and Diabetic Neuropathy was done by subjective criteria i.e., symptoms and object criteria i.e. by Monofilament Test, Vibration Test and Reflexes Study. This study show that subject having Diabetes Mellitus history more than five years had Dushti of Majjadhatu and developed the symptoms of Diabetic peripheral neuropathy. This study also shows that symptoms of Diabetic peripheral neuropathy can be correlated with Majjapradoshajavikara. Present study indicated that Majjadhatu (Nervous system) gets vitiated in Madhumeha (Diabetes Mellitus).